Vereenigde Oostindische Compagnie (VOC) Trade Accounting as an Instrument of Colonial Power: A Case Study of Palembang Darussalam in the 18th Century - Hilda Hilda; Endang Rochmiatun; Mohammad Syawaludin; Wijonarko Wijonarko (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study examines the accounting practices of the Vereenigde Oostindische Compagnie (VOC) in Palembang during the Palembang Sultanate, which not only represented economic activities but also functioned as a tool of colonial power. Trade activities at that time involved relationships between regions, kingdoms, sultanates, and foreign countries. The VOC, as the representative of the Dutch, conducted accounting records in trade activities in Palembang. This study aims to reveal how VOC accounting practices became part of the economic and political domination strategy over the Palembang Sultanate. The study employs Social Construction Theory and Conventional Accounting Theory. The method used is qualitative with a heuristic approach to 18th-century VOC archives. Data was collected through document studies, archives, photographs, and manuscripts obtained from the National Archives of the Republic of Indonesia and private collections. The findings reveal that VOC accounting practices were not neutral activities but were used to control commodity flows, set prices, and negotiate local power. These practices reflect efforts to strengthen colonial hegemony through accounting instruments. The findings of this study confirm that VOC economic record-keeping during the Palembang Sultanate was an important part of colonial economic and political strategy. Additionally, this research contributes to colonial history studies by demonstrating that trade archives are not merely sources of economic data but are also rich in ideological and power-related meanings.